PELAYANAN BERKUALITAS DAN KEPERCAYAAN: KUNCI MEMBANGUN LOYALITAS NASABAH - Tukinah, Ukie; Tamrin, Moh; Adi Nugroho, Bayu Sapta (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2025)
This research aims to determine the influence of service quality and customer trust on customer loyalty at BRI Bank Warungasem Unit, in Batang Regency.Loyalty is a customer's deep commitment to repeat subscriptions. The population in this research is Bank BRI Warungasem Unit customers with a total of 956 customers and a sample taken using the Slovin formula of 100 people. The independent variables of this research include service quality (X₁) customer trust (X2) while the dependent variable is customer loyalty (Y). Data was collected using a questionnaire that had been tested for validity and reliability. The data analysis technique used in this research is multiple regression with the help of calculations via the SPSS application. The test results obtained for the Service Quality variable obtained tcount = 2.016 more than t table 1.66023 with a significance level of 0.047 (less than 0.05). Thus, it can be concluded that Service Quality has an influence on Customer Loyalty at Bank BRI Warungasem Unit, and the test results obtained for the Customer Trust variable obtained tcount = 9.646 more than t table 1.66023 with a significance level of 0.000 (less than 0.05). Thus, it can be concluded that Customer Trust has an influence on Customer Loyalty at Bank BRI Warungasem Unit. The coefficient of determination value denoted in the Adjusted R Square number is 0.724, this means that the contribution of the influence of the Service Quality (X1) and Customer Trust (X2) variables to Customer Loyalty (Y) is influenced by 72.4%. Thus, 27.6% (100%-72.4%) is influenced by other variables that influence customer loyalty such as customer satisfaction, comfort, location and others. Suggestions for Bank BRI Warungasem Unit are that periodically, bank administrators or management need to prepare programs to improve bank services to customers with the aim of maintaining and increasing bank customer loyalty. For example, by giving rewards to customers who have joined and contributed to the bank for a long time, increasing the largest effective contribution that influences the Customer Loyalty variable is the Customer Trust variable, so the Bank should always maintain credibility and improve the quality of bank services so that Bank BRI Warungasem Unit customers always have the trust of their customers.